A Review of the Book “The Paleolithic Settlement of Asia” - Seyyed Milad Hashemi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Professor Robin W. Dennell is a well-known British archaeologist specialized in Asian Paleolithic studies. One of his books, entitled “The Paleolithic Settlement of Asia”, published by Cambridge University Press, is reviewed here. It is considered a skillful synthesis of archaeological, paleoanthropological, and paleoclimatological evidence of Early and Middle Pleistocene periods in Asia. The book comprises some important and rather innovative ideas about the subject which the author had been developing during his academic life; for instance, among them are the idea of the presence of an extensive grassland belt stretching from northeast Africa to east Asia during Early Pleistocene, which facilitated the dispersal of hominins out of Africa (Out of Africa I). Another novel hypothesis that is discussed in the book is the controversial idea that Asia could be considered where Homo erectus was originated. Apart from what is mentioned, a large part of the book is dedicated to the climatic fluctuations and the evolution and dispersal of hominins during Early-Middle Pleistocene periods. The evidence used in the book has been recovered from well-known archaeological sites containing hominin fossils and faunal remains, as well as from major maritime and continental sites within which paleoclimatic investigations have been conducted. The mentioned book is considered one of the pioneering attempts to modify the absolute Afrocentric view in Lower Paleolithic Archaeology.